2014
DOI: 10.5194/nhess-14-2069-2014
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoclimate and palaeoseismic events discovered in Diexi barrier lake on the Minjiang River, China

Abstract: Abstract. Studies on the formation of the ancient Diexi barrier lake on the Mingjiang River, southwestern China, have long been carried out. However, investigations into the correlation between the palaeoclimate and palaeoenvironment and the palaeoseismic events in this area are rarely found in literature. The present study took sediments from the ancient Diexi barrier lake to investigate the palaeoclimate, palaeoenvironment and palaeoseismic events. A drilling at the centre of the barrier lake was conducted a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…old Quaternary lacustrine deposits in Diexi, eastern margin of the Tibetan Plateau, Sichuan, China, indicated the possible existence of an enormous, late Pleistocene rockslide dam (Wang et al 2005;Wang and Meng 2008;Dai et al 2021). Direct dating evidence advocates that the paleo-landslide dam appears to have survived more than 10,000 years in total (Wang et al 2014b), making it indefinitely the oldest of such features within longest ever lasted (and dated) natural dam in recent geological time worldwide as per the author's know-how. Prior to the work of this article's authors, no attempts had been made to understand the internal structure of the Diexi paleo landslide dam, which made it an excellent candidate for site-specific studies to characterize the likely evolution of such features.…”
Section: Original Papermentioning
confidence: 99%
“…old Quaternary lacustrine deposits in Diexi, eastern margin of the Tibetan Plateau, Sichuan, China, indicated the possible existence of an enormous, late Pleistocene rockslide dam (Wang et al 2005;Wang and Meng 2008;Dai et al 2021). Direct dating evidence advocates that the paleo-landslide dam appears to have survived more than 10,000 years in total (Wang et al 2014b), making it indefinitely the oldest of such features within longest ever lasted (and dated) natural dam in recent geological time worldwide as per the author's know-how. Prior to the work of this article's authors, no attempts had been made to understand the internal structure of the Diexi paleo landslide dam, which made it an excellent candidate for site-specific studies to characterize the likely evolution of such features.…”
Section: Original Papermentioning
confidence: 99%
“…Furthermore, in the downstream regions of landslide dams, evidence of outburst sediment may also be well preserved for thousands of years (Cutler et al, 2002;Carling, 2013;Chen et al 2018). In the Diexi Region, it was observed that thick lacustrine sediment had extended in the upper reach of the Diexi landslide dam of the Minjiang River for tens of thousands years, with a length of approximately 30 km and a maximum thickness of more than 200 m (Wang et al, 2014b;Ma et al, 2018;Xu et al, 2020). In addition, it has been found that below the dam, the high-energy outburst floods delivered coarse diamict boulders from the landslide dam to the downstream areas.…”
Section: Geomorphological Effects Of the Dall And Llofsmentioning
confidence: 99%
“…This lake initially received widespread attention in the research studies which were conducted regarding the Diexi earthquake of 1933. A large number of in-depth examinations of the lacustrine sediment in the upstream area of the landslide dam were completed in the decades following the aforementioned earthquake event (Wang et al, 2011;Wang et al, 2014b;Wei et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The valley cutting depth is more than 800 m, and the maximum cutting depth can reach 3,000 m (Jiang et al, 2014). The epicentre of the 1933 Diexi earthquake, where the Songpinggou fault and Minjiang fault converge (Wang et al, 2014a;Ma et al, 2018), is approximately 5.5 km southwest of the Diexi section. Landslides triggered by the Diexi earthquake are mainly distributed in Songpinggou; in addition, some landslides occurred near Diexi town (Ren et al, 2018).…”
Section: Geological and Geographical Settingsmentioning
confidence: 99%